2022
DOI: 10.3390/cancers14246024
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p16 and Its Relationship with Human Papillomavirus Status in Patients with Penile Squamous Cell Carcinoma: Results of 5 Years Follow-Up

Abstract: Penile Squamous Cell Carcinoma (PSCC) is associated with high-risk human papillomavirus (HR-HPV). The immunohistochemical (IHC) test for p16INK4a (p16) is highly correlated with HR-HPV expression in other SCCs. To investigate whether the expression of p16 IHC or HR-HPV is associated with survival in PSCC, we conducted a single institution analysis of 143 patients with a diagnosis of PSCC and, available tissue were tested for p16 IHC staining patterns, histological subtype, tumor grade, and lymphovascular invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Positive p16 expression was found in XPe3, XPe9, and XPe16 lysates in the immunoblot that correlated with the p16-positive assignments using our hybrid IHC-scoring method. For XPe20 and XPe821, PDX lysates had little to no p16 expression based on immunoblotting and they were considered p16-negative using our hybrid IHC-scoring method [ 10 ]. We did not observe HPV16 E6 or E7 transcripts in Pe20 patient tissue and we observed the transcripts for both proteins in XPe821.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive p16 expression was found in XPe3, XPe9, and XPe16 lysates in the immunoblot that correlated with the p16-positive assignments using our hybrid IHC-scoring method. For XPe20 and XPe821, PDX lysates had little to no p16 expression based on immunoblotting and they were considered p16-negative using our hybrid IHC-scoring method [ 10 ]. We did not observe HPV16 E6 or E7 transcripts in Pe20 patient tissue and we observed the transcripts for both proteins in XPe821.…”
Section: Discussionmentioning
confidence: 99%
“…We used our recently published hybrid system (HS) for analyzing p16 via IHC. The HS method uses both the percentage (>75%) of positive staining of the tumor section and the staining pattern [ 10 ]. In the HS method, tumor tissues with a positive staining of >75% and a pattern of 3 or 2 are considered positive for p16, whereas those with a staining pattern of <75% and a staining pattern of 2, 1, or 0 are considered negative for p16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, p16 ink4a (a cyclin-dependent kinase inhibitor) is inhibited by Rb protein [80,81]. Thus, HPV E7-induced blocking of Rb function can increase p16 ink4a expression in PC via a feed-back control [82][83][84]. Even though up-regulation of p16 ink4a expression has been observed during HPV infection, several studies have demonstrated that the p16 ink4a gene can be methylated.…”
Section: Hpv + Pc Genome Methylationmentioning
confidence: 99%
“…The development of PSCC is frequently linked to multiple risk factors, such as inadequate hygiene, absence of circumcision, tobacco smoking, specific genetic conditions, and the presence of HPV, which can be found in 30-50% of cases [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%